Density functional study Structures, Stabilities and Energetic properties of Gen (n= 2-30) clusters - Benaida, M.; Aiadi, K.E.; Mahtout, S.; Bentouila, O.; Djaadi, S. (University of Eloued جامعة الوادي, 2018)
The lowest energy structures of Gen (n=2–30) clusters are obtained using the first principles pseudopotential simulated annealing within the generalized gradient approximation (GGA) of density functional implemented in SIESTA method. New low-energy structures are obtained for each cluster size. The optimized clusters reveal that the most stable structures and their corresponding isomers have three dimensional configurations. The relative stabilities in terms of the binding energies, fragmentation energies and second-order difference of energies for all Gen (n=2–30) structures have also been investigated and discussed.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Ge Clusters, Density functional theory, simulated annealing, Structural properties, SIESTA.